2016
DOI: 10.1371/journal.pone.0149989
|View full text |Cite|
|
Sign up to set email alerts
|

Why Do You Believe in God? Relationships between Religious Belief, Analytic Thinking, Mentalizing and Moral Concern

Abstract: Prior work has established that analytic thinking is associated with disbelief in God, whereas religious and spiritual beliefs have been positively linked to social and emotional cognition. However, social and emotional cognition can be subdivided into a number of distinct dimensions, and some work suggests that analytic thinking is in tension with some aspects of social-emotional cognition. This leaves open two questions. First, is belief linked to social and emotional cognition in general, or a specific dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
77
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 107 publications
13
77
2
5
Order By: Relevance
“…Rather, results agree with reports suggesting a negative association between religiosity and analytic thinking as shown in academic studies that evaluate arguments related to beliefs (Tinoco, 1998;Jack et al, 2016). Accordingly, tension between religiosity and analytic thinking is present in the participant's testimonies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rather, results agree with reports suggesting a negative association between religiosity and analytic thinking as shown in academic studies that evaluate arguments related to beliefs (Tinoco, 1998;Jack et al, 2016). Accordingly, tension between religiosity and analytic thinking is present in the participant's testimonies.…”
Section: Discussionsupporting
confidence: 88%
“…However, morality is so influenced by religious beliefs that some authors propose that brain functions related with moral concern and those related to analytic thinking are in tension (Jack et al, 2016). Along these lines, some fMRI studies have shown that while performing deontological moral judgments Catholic practitioners recruit the precuneus and temporoparietal junction, but activate the dorsolateral prefrontal cortex and temporal poles while performing utilitarian judgments.…”
mentioning
confidence: 99%
“…Item bias still has the potential to explain part or all of these relationships, as it did recently for the results of an actively open-minded thinking questionnaire [28]. It remains possible-though we were unable to test this-that these results may be explained by other mediators such as death salience, moral concern, conformism, attachment style, executive control, or analytical thinking style [29][30][31][32].…”
Section: Discussionmentioning
confidence: 71%
“…This is important. But follow-up studies failed to replicate the previously observed negative association between autism and supernatural beliefs (Jack, Friedman, Boyatzis, & Taylor, 2016;Maij, van Harreveld, et al, 2017). Importantly, in a large sample collected in the US and the Netherlands, the variance of autistic traits in explaining religious belief was close to zero.…”
Section: Individual Difference Studiesmentioning
confidence: 77%